Impact-induced muscle damage: Performance implications in response to a novel collision simulator and associated timeline of recovery - Naughton, M.; Miller, J.; Slater, G. J. (Journal of Sports Science & Medicine, 2018)
The implications of impact-induced muscle damage (IIMD) that results from participation in contact-sport are not well understood. The purpose of the present study was to implement a novel method of generating IIMD and characterise the implications of this on perceptual, biochemical and exercise performance parameters. Eighteen male recreational contact-sport athletes completed a single-group time series with measures assessed at baseline (PRE) and immediately following (POST) an IIMD protocol, with repeat testing 24, 48, and 72 h following the IIMD protocol. Biochemical indices of muscle damage (myoglobin [Mb]) and inflammation (high-sensitivity C-reactive protein [hs-CRP]), 15 m sprint performance, squat jump peak power (SJ-PP), and perceived soreness were compared to PRE using a one-way (time) repeated measures ANOVA with post-hoc t tests. Speed over 5 and 15 m were impaired for 48 h (7.5 ± 4%, p < 0.01) and SJ-PP was impaired for 48 h following the IIMD protocol (9.5 ±3 %, p < 0.01). Subjective soreness was elevated from baseline for 72 h (P < 0.01) following the IIMD protocol. No change in [CRP] or [Mb] was observed (p > 0.01). IIMD resulted in impaired ability to produce power and speed, whilst negatively influencing perceived soreness. These changes were most pronounced in the 48 h following the IIMD protocol. No change in muscle damage or inflammation indices were observed, primarily due to the highly variable response. Thus, the experimental protocol used in the present study may be used as a model to further investigate other aspects of IIMD.